PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 005 RANTAU PANJANG KIRI - Daud, Damanhuri; ', Indayati; ', Hj. Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study was motivated by the percentage of students who achieve KKM 70 on odd semester 2014/2015 is still low. Of the 20 students, only 9 (45.00%) of students who reach KKM and 11 (55.00%) students who have not reached KKM with an average grade 62.85. This is because teachers do not use teaching model during the learning process in the classroom. Of these problems is necessary to study a class action by applying the Guided Inquiry learning model. The place is a study in SDN 005 Rantau Panjang Kiri with research subjects are students of class IV of 20 people, boys 9 and 11 female students. This study was conducted in two cycles. Data collection instruments in this research is to test daily tests, observation of student activity sheets and sheets of observations of teacher activity. The results showed that the learning outcomes of students has increased, the base score with an average of 62.85 increased in the first cycle to 74.00 with the percentage increase of the base score to the first cycle of 17.74%. In the second cycle increased to 83.00 with the percentage increase of the base score to cycle II of 32.06%. Mastery learning students in the first cycle showed that 70.00% reaching KKM predetermined by category classical completeness is not completed and the second cycle increased to 90.00% with the category of classical completeness completed. Observations show that the activity of students and teachers also increased. Student activity at the first meeting (55.00%) increased in the second meeting (70.00%) and then at the first meeting of the second cycle increased (80.00%) and at the meeting of 2 increase (85.00%). The activities of teachers in the first cycle 1 meeting at 60.00% increase in the second meeting (75.00%) and the second cycle the first meeting increased by 80.00% in the second meeting increased (95.00%). From the above shows that through the implementation of Guided Inquiry Learning Model to improve learning outcomes IPA grade IV SDN 005 Rantau Panjang Kiri academic year 2014/2015.Keyword : Guided Inquiry Learning Model, Science Learning Result